IT SUPPORTS TO IMPROVE THE FINANCIAL LITERACY OF THE MUSHROOM FARMERS COMMUNITY IN CENTRAL JAVA, INDONESIA - Agustina Fitrianingrum; Yuli Indah Sari; Hanif Ahmadi (Universitas Internasional Batam, 2022)
There are numerous researches explained that the number of entrepreneurs in a country is frequently used as an indicator of national economic growth. Instead of the number, the size of business is also important as the driver of economic growth. In Indonesia, the number of Micro Small, and Medium Enterprises (MSME) in 2019 is nearly 120 million. Unfortunately, the size is dominantly by the micro and small business which is around 98% of the total MSME. Responding to the phenomena, the academician put some efforts to empower MSME entrepreneurs, especially to manage the financial report. The ability to manage the financial aspect is the very basic requirement for a business can grow in healthy conditions. In the broader area, this project is aimed to support the UN Sustainable Development Goal number 8, Decent Work and Economic Growth. The project to improve the financial literacy of MSME is conducted in Jepara, Central Java which is focused on the Mushroom Farmers Community. The purpose of the project is to improve the quality of financial reports to help them be able to get financial support from the bank. The application used is built by one of the Indonesian National Bank, which is focused to deliver their services for farmers. Hence, the group of mushroom farmers and community trained to use the application, namely Stroberi. The project has been starting in the last quarter of this year. Thus, it is expected that when the farmers have a full annual financial report, they will be able to have a financial report which follows the standard.